Analysis of Internal Control of Accounts Receivable for Travel Agents at Four Seasons Resort at Jimbaran Bay - Ni Putu Novie Amelia Putri; Ni Ketut Mareni; I Putu Arnawa (Transpublika Publisher, 2025)
Four Seasons Resort at Jimbaran Bay has experienced a significant increase in accounts receivable balance every year. Based on the table of sources of credit sales and the amount of accounts receivable balance for the period 2021 to 2023, it shows that the largest accounts receivable balance comes from travel agents, accompanied by a slow turnover rate of receivables. This indicates that the collection process of receivables has not been functioning well and poses a risk of uncollectible receivables which impacts the hotel’s operational cash flow. This research seeks to assess the internal controls related to travel agent receivables at the Four Seasons Resort Jimbaran Bay from 2021-2023 by the application of the COSO (Committee of Sponsoring Organizations of the Treadway Commission) framework. A qualitative data analysis method was employed, utilizing triangulation of primary and secondary data from interviews and observations to ensure credibility and validity. Findings shows that the internal control over receivables at the Four Seasons Resort at Jimbaran Bay is still not optimal in terms of the five existing components. The implementation of the risk assessment component for monitoring activities has not been optimally executed. Thus, improvement is needed to avoid the risk of uncollectible receivables. Meanwhile, the control environment component, control activities, information, and communication have been operating optimally as seen from the performance of employees which is in accordance with the operational standards set by the company.